Field Study of the Noise Exposure Inside Running Metro Unit - Younes, Mohamed N.; Heikal, Ali Z.; Kotb, Akram S.; Zohny, Haytham N. (Salehan Institute of Higher Education, 2021)
The noise levels inside metro units are considered a significant problem that makes passengers suffer from severe damage, especially for those who use the metro periodically. This research evaluates the acoustic environment inside the metro car and studies factors affecting the noise levels inside metro units and developing models for estimate noise in the metro unit while moving between stations. Greater Cairo Metro (GCM) Line 1 has been selected as a case study. A sound level meter was used to measure the equivalent sound level in dBA and evaluate the noise inside metro units. The results indicate that the noise levels are unacceptable compared with the international noise exposure standards. The highest measured noise level inside metro units is 91.2 dBA. These unacceptable noise levels led to more investigation of factors that may affect noise levels inside metro units. Other data have been collected, such as the speed of the train and the track alignment details. The results showed that the noise increases with the increase of the train speed until the speed reaches a specific value, then it decreases depending on the maintenance status and the train type. In addition, the noise levels through curved underground tracks are higher than the levels along straight surface tracks by 18 dB(A).Â Doi: 10.28991/cej-2021-03091674 Full Text: PDF